VISIBLE LIGHT PHOTODEGRADATION OF DIISOPROPANOLAMINE IN WASTEWATER USING PHOTOCATALYST BASED ON CeO2-TiO2 - SIVALINGAM, JAGATH RETCHAHAN (2020)
Nanomaterial has been used for various applications such as wastewater treatment, organic and inorganic material degradation as well as industrial applications. Biological treatment method through aerobic and anaerobic treatments provides minimal level of degradation. Diisopropanolamine (DIPA) used in processing industry is not fully converted in the recycling process, carried into wastewater system therefore endangering the biological systems in water. TiO2 suffers from few drawbacks in its 4% UV absorption range which is below 400 nm and high band gap energy of 3.2 eV. In this study, wastewater containing diisopropanolamine produced from the oil and gas industry was treated via photodegradation process.